Musical Influence on Language Development: Comparing Popular and National Songs in Children - Hapsari, Sinta Maulida; Aisyah, Laily Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
Music plays a crucial role in early childhood language development, yet comparisons between popular and national songs remain limited. This study employed a comparative intervention approach to examine the effects of song type on linguistic imitation and memory in children aged 5–6 years. Sixty children from five preschools in Jember City, Indonesia, were purposively sampled and divided into two groups of 30, exposed to either popular or national songs. Structured musical sessions, conducted twice weekly over four weeks, included guided listening, singing, imitation, and memory tasks. Children’s performance was observed using structured instruments and audio recordings. Data were analyzed with descriptive statistics and independent t-tests. Results showed that popular songs significantly enhanced linguistic imitation, while national songs improved memory retention. These findings highlight the role of song structure, repetition, and familiarity in shaping language and memory outcomes, providing practical guidance for early childhood educators to strategically integrate popular and national songs for cognitive, linguistic, and socio-cultural development.